Outside the walls of Intramuros - Garrido, Wilfredo 1960- (Gondola Books, 2008)
"The year is 1898. The Spanish Empire falls. America rises. The Philippines loses its bid for freedom. An epic story of war and adventure, romance and betrayal, filled with flawed characters and lessons for the 21st Century. The author fills his story with ironies and villains that bring back vividly a forgotten era when America fought a colonial war in the Pacific"--Publisher description.